2012
DOI: 10.1007/s12610-012-0161-4
|View full text |Cite
|
Sign up to set email alerts
|

Glandular amputation after circumcision

Abstract: Résumé Introduction Sous nos climats, la circoncision reste l’intervention la plus couramment pratiquée chez le garçon. Elle est souvent réalisée par un personnel paramédical non qualifié, ou même en dehors du milieu médical dont les notions de chirurgie et d’asepsie sont aléatoires. Elle est réputée comme chirurgie bénigne, mais des complications majeures parfois très graves, engageant le pronostic sexuel, voire vital, peuvent survenir. Le but de ce travail était de rapporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…Its frequency is differently reported in the literature. MSEDDI et al [19] reported eight cases of glans amputation following traditional circumcision in Tunisia, whereas in Côte d'Ivoire, Dieth et al [9] collected four cases in fourteen years. Contributing factors cited were: the child's flailing during foreskin sectioning, live circumcision (without anesthesia), and failure to follow the various stages of circumcision [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its frequency is differently reported in the literature. MSEDDI et al [19] reported eight cases of glans amputation following traditional circumcision in Tunisia, whereas in Côte d'Ivoire, Dieth et al [9] collected four cases in fourteen years. Contributing factors cited were: the child's flailing during foreskin sectioning, live circumcision (without anesthesia), and failure to follow the various stages of circumcision [10].…”
Section: Discussionmentioning
confidence: 99%
“…For ritual circumcision, particularly in our country, the foreskin and its mucous membrane are cut transversely at the same time, after good traction on the foreskin by the operating assistant. This section is performed after wedging and pushing down the glans between the thumb and forefinger, or at best, after placing a clamp over the glans previously located by the fingers [19]. Therapeutic management depended on how soon the patient was seen after the accident, and the conditions under which the severed glans was transported.…”
Section: Discussionmentioning
confidence: 99%